Exploring organic food purchase intention in Bangladesh: an evaluation by using the theory of planned behavior - Mahmudur Rahman, Khandoker; Mohd Noor, Nor Azila (Medwell Journals, 2016)
The recent growth of organic food sector has contributed to the growth of consumer research in this area.The rise in consumer research related to organic food is particularly evident in the Western hemisphere.Past scientific studies provided evidence that organic foods confer multiple promises to future generations.Some of the promises were sustainable food production, food security, food safety, nutrition and reduction of green-house gas impacts, etc. Despite all these promises, research under Asian context may still be considered low.Specifically under Bangladesh context, only a few investigations could be traced that actually examined consumer behavior under a well-grounded theoretical framework.The current study employs an empirical approach to achieve its two-fold objectives.First, it looks into the fundamental determinants of organic food purchase intention and their underlying relationships by using the theory of planned behavior.Consequential to the first objective, the study is also aimed at inferring whether the theoretical framework maybe adopted as the baseline model in future studies as well.It seems that this might be a pioneering study that would be examining the aforesaid theoretical framework under Bangladesh context. The empirical findings indicate that attitude and subjective norm are significant determinants of purchase intention where as perceived behavioral control is not significant.It is also found that the theory of planned behavior may be applied in modeling consumers’ purchase intention since the statistical model fit is satisfactory.